2013
DOI: 10.2500/aap.2013.34.3705
|View full text |Cite
|
Sign up to set email alerts
|

A patient preference and satisfaction study of ciclesonide nasal aerosol and mometasone furoate aqueous nasal spray in patients with perennial allergic rhinitis

Abstract: Patients' preference and satisfaction with their nasal allergy medications may be influenced by their sensory attributes. This study evaluates patient preference and satisfaction with ciclesonide hydrofluoroalkane nasal aerosol (CIC-HFA) compared with mometasone furoate aqueous nasal spray (MFNS). Symptomatic subjects with perennial allergic rhinitis (PAR) were randomized to CIC-HFA at 74 micrograms or MFNS at 200 micrograms q.d. in an open-label, two-period, crossover study. Subject preference was recorded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…However, an open-label randomized crossover study found a similar incidence of epistaxis when comparing ciclesonide hydrofluoroalkane and mometasone furoate: 2.3% and 1.3%, respectively. 20 Our study supports this finding, as we noted that all 4 studies looking at (ciclesonide hydrofluoroalkane) reported epistaxis as an adverse event. 19,20,33,38 The studies using non–FDA-approved INCS did not include epistaxis as a complication of medication usage.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, an open-label randomized crossover study found a similar incidence of epistaxis when comparing ciclesonide hydrofluoroalkane and mometasone furoate: 2.3% and 1.3%, respectively. 20 Our study supports this finding, as we noted that all 4 studies looking at (ciclesonide hydrofluoroalkane) reported epistaxis as an adverse event. 19,20,33,38 The studies using non–FDA-approved INCS did not include epistaxis as a complication of medication usage.…”
Section: Resultssupporting
confidence: 87%
“…Epistaxis was noted in more than half of the articles included in our study. 16-49 The most commonly reported medications with this drug effect include fluticasone propionate, fluticasone furoate, and mometasone furoate. However, an open-label randomized crossover study found a similar incidence of epistaxis when comparing ciclesonide hydrofluoroalkane and mometasone furoate: 2.3% and 1.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding local effects, a recent study demonstrated that ciclesonide, a pro-drug, has local adverse effects similar to mometasone, which is not a pro-drug [ 7 ], suggesting that clinical translation of preclinical data is not necessarily linear. In conclusion, it is diffi cult at present to establish which new-generation GC should be the fi rst choice.…”
Section: New Generation Of Topical Gcsmentioning
confidence: 97%
“…A first generation corticosteroid, dexamethasone, is no longer preferred due to its side effects ( 452 ). The second generation corticosteroids, including beclomethasone dipropionate (aerosol) ( 453 - 460 ), budesonide (aqueous) ( 461 - 463 ), ciclesonide (aqueous or aerosol) ( 464 - 466 ), flunisolide (aqueous), fluticasone furoate (aqueous) ( 467 - 470 ), fluticasone propionate (aqueous) ( 471 - 474 ), triamcinolone acetonide (aqueous) ( 475 - 476 ) and mometasone furotate (aqueous) ( 466 , 477 - 482 ) have been used in nasal spray preparations until today.…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%